Microwave-Synthesized NiO as a Highly Sensitive and Selective Room-Temperature NO2 Sensor. (1st January 2018) - Benedict, Samatha; Singh, Monika; Naik, T. R. Ravikumar; Shivashankar, S. A.; Bhat, Navakanta
Abstract : In this work, we report microwave-assisted deposition of NiO for application as room- temperature NO2 sensor. The synthesis conditions are varied to arrive at the optimum film for sensing NO2 . The optimum NiO film shows response of 4991% at 3 ppm NO2 at room temperature with short response and recovery times of 30 s and 45 s, respectively. X-ray diffraction reveals the cubic structure of the NiO film with slightly preferred orientation and scanning electron microscopy shows high porosity in the film, both contributing to the enhanced sensing performance. The microwave-synthesized NiO shows an order of magnitude stronger response to NO2 (3 ppm) at room temperature operation than does optimized, DC-reactive-sputtered NiO operating at 175°C. To the best of our knowledge, this is the first report on room temperature detection of NO2 by a microwave-synthesized NiO film. The detection limit of the NiO film is 200 ppb with good selectivity against interfering gases. The sensor demonstrates an ultra-low power consumption of 0.2 μW, making it suitable for solar-powered pollution-monitoring.